Pregnancy Complicated by Acute Pancreatitis with Ascariasis - Thakur, S. K.; Dangal, G.; Karki, A.; Pradhan, A.; Shrestha, R.; Bhattachan, K.; Bajracharya, N.; Tiwari, K.; Bharati, S.; Maharjan, O.; et al. (Kathmandu University Medical Journal, 2020)
Ascariasis lumbricoides infections are common in tropical and sub-tropical countries. As it is one of the common causes for common bile duct obstruction. But in pregnancy is a rare entity. It may present with complications like acute pancreatitis. Here we present a case of 24 year female gravida 2 para 1 at 34 weeks of pregnancy presented with chief complain of pain over epigastric region radiating to back and associated with two episodes of vomiting, non bilious, not mixed with blood. Ultrasonography showed long tubular hyperechoic structure in gallbladder lumen most likely ascariasis and then she was diagnosed as a case of acute pancreatitis with alive ascariasis.